Innovative E-Learning Strategies of Islamic Religious Teachers: A case study at a public faith-based high school in Jambi, Indonesia - Safitri, Chairun Nisa; Joko Susilo, Mohamad (Journal of Pedagogy and Education Science, 2024)
The success of a learning process depends on the strategies educators use, including skills in presenting face-to-face and virtual lesson material, such as e-learning. This research aims to determine teachers' strategies in the Islamic Religious Education learning process by implementing e-learning as a learning medium at a public faith-based high school in Jambi, Indonesia. This research uses a descriptive qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation. The research subjects were Heads of schools, Islamic religious education teachers, and students. Data analysis techniques follow Miles and Huberman's phases. The research results show that the use of e-learning as a learning medium involves three stages of learning planning before implementation, followed by learning implementation, where the teacher delivers the material and uses PowerPoint. Finally, the teacher evaluates learning by giving assignments and daily tests.